ANALISIS PERENCANAAN DAN PENGAWASAN BIAYA PRODUKSI - Riyandi, Rahmat (EQUILIBIRIA, 2019)
This thesis analyzes the planning and supervision of the Production Costs PT. Dwi Sumber Arca Waja, reasons for selecting the title because the authors wanted to know how to plan and control production costs at PT. Dwi Sumber Arca Waja. Issues to be answered in this study is whether the cost of production at PT. Dwi Sumber Arca Waja is in accordance with good planning, whether the cost of production at PT. Dwi Sumber Arca Waja is in conformity with good supervision.